Potensi Metabolit Sekunder Cendawan Endofit Tanaman Cabai sebagai Penghambat Fusarium sp. Patogen Asal Biji Secara in Vitro - Dewi Novina Sukapiring; Bonny Poernomo Wahyu Soekarno; Titiek Siti Yuliani (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Endophytic fungi was known as controlling agents to pathogenic fungi, including Fusarium oxysporum. This research was aimed to select endophytic fungi from pepper which produced secondary metabolites and have beneficial effect in controlling seed borne pathogen especially Fusarium sp. Four isolates was obtained, i.e. CECL 19, CECL 28, CECL 38, and CECL 40; and further examined in 3 media fermentation, i.e. yeast glucose broth, potato dextrose broth, and potato dextrose yeast broth. Metabolites of endophytic fungi was tested in vitro for its inhibition effect on the growth of Fusarium sp. The result showed that the type of fermentation medium was significantly determining the ability of endophytic fungi in inhibiting the growth of Fusarium sp. Medium PDA and DEC was determined as the best medium to optimize metabolite production of CECL 28 and CECL 18, respectively. Metabolite compound produced by CECL 28 has been effective to inhibited Fusarium sp.